Geometria das rochas ferríferas da região de Pedra Branca do Amapari (Amapá) - SEGUNDO, Roberto Barbalho Leal (2019)
This study presents structural data undertaken during geological mapping (1:2.000) on an area of about 5 km2 located on the Projeto Predra Branca do Amapari (AP), under the Anglo Ferrous mining control. The research was based on structural mapping (geometrical and kinematics analysis). The regional tectonic framework is characterized by sets of holomorphic folds starting, in the E of the region, with a isoclinal synform plunging 15/340 with flanks dipping moderately towards SW. This set shows a NE vergence (mass flow from SW towards NE). Towards SW occurs a kilometer-scale open antiform, showing low-angle parasitic folds (M geometry). Two main iron-rich rocks are identified on the mines: (1) continuous milimetre-scale banded rocks with typical silica/iron intercalations; these rocks are folded in parasitic sets suggesting a flexural folding mechanism. The second rock type is characterized by (2) an anastomosed myloniic foliation, NW-SE oriented, with dips that vary from 20° to subvertical . The folds on the foliation show low-angle plunges (subhorizontal to 20°) towards NW. A later ductile brittle E-W shear zone cuts all the mine rocks. Pegmatite bodies are present in almost all the rocks. They are very irregular im shape, reflecting their late emplacement along dilational spaces formed due the deformation of the rocks. At the end of this work, a geometrical and kinematics model is presented based on the partially sheared fold flanks, in different scales.